2011
DOI: 10.1586/erv.11.15
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virosomes as a vaccine adjuvant and carrier system

Abstract: Influenza virosomes have been used for more than 10 years in commercial vaccines. The technology has been further developed as a carrier and adjuvant system for subunit vaccines, in particular for synthetic peptides. The extensive amount of preclinical and clinical data supports the notion that influenza virosomes represent a platform technology that ensures robust and long-lasting immune responses against subunit antigens with an excellent safety profile. Structurally and functionally, virosomes are enveloped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(65 citation statements)
references
References 93 publications
2
61
0
2
Order By: Relevance
“…At both age extremes, Th1 responses and sufficient cytotoxicity of lymphocytes have to be improved, e.g. by use of adjuvants [42,44,45,46], by concomitant vaccination with other vaccines [22], by change in antigen concentrations, e.g. high-dose vaccines for influenza [40] or zoster [39] in the elderly, or implementation of other dose intervals [15,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At both age extremes, Th1 responses and sufficient cytotoxicity of lymphocytes have to be improved, e.g. by use of adjuvants [42,44,45,46], by concomitant vaccination with other vaccines [22], by change in antigen concentrations, e.g. high-dose vaccines for influenza [40] or zoster [39] in the elderly, or implementation of other dose intervals [15,20].…”
Section: Discussionmentioning
confidence: 99%
“…A very long experience exists with adjuvants in seasonal influenza vaccination, such as MF59 [44,45] and virosomes [46], increasing efficacy of influenza vaccination by inducing specific CD4+ T cell responses, strong and long-lasting memory T and B cell responses and by broadening the immune responses beyond the influenza strains included in the actual vaccine [44] with a favorable outcome also in small children [45]. …”
Section: Approaches To Enhance Immunogenicity Of Vaccinesmentioning
confidence: 99%
“…Virosomes are spherical lipid vesicles that include the functional viral glycoproteins haemagglutinin and neuraminidase from influenza [77] and can be regarded as uni-lamellar liposomes carrying the spike proteins of influenza virus on their surface [78].…”
Section: Virosomesmentioning
confidence: 99%
“…The influenza HA antigen targets the virosomes to APCs, which engulf it by endocytosis and present the antigens to T cells after proteolytic degradation. Pre-existing immunity against influenza may represent another important determinant for the immunostimulating effect of virosomes [77].…”
Section: Virosomesmentioning
confidence: 99%
“…Recent studies have showed that virus-related products such as the defective interfering (DI) RNA produced by the Sendai virus strain Cantell [19] or influenza virosomes [20] can efficiently work as viral vaccine adjuvants. We recently identified two linear determinants of gpG VHSV (peptides p31 and p33) implicated in triggering a cell antiviral response mediated by type I IFN [21].…”
Section: Introductionmentioning
confidence: 99%